![](https://rs.olm.vn/images/avt/0.png?1311)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
a)(|x-2|-3)(5+|x|)=0
<=>|x-2|-3=0 hoặc 5+|x|=0
*)Xét |x-2|-3=0 <=>|x-2|=3
=>x-2=±3
Với x-2=3 =>x=5
Với x-2=-3 =>x=-1
*)Xét 5+|x|=0
=>|x|=-5 (mà \(\left|x\right|\ge0>-5\) với mọi x)
=>vô nghiệm
(2x-1)2=1-2x
<=>4x2-4x+1=1-2x
<=>4x2-2x=0
<=>2x(2x-1)=0
<=>x=0 hoặc x=\(\frac{1}{2}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
A=x2−4x+1=(x−2)2−3≥−3A=x2−4x+1=(x−2)2−3≥−3
⇒Amin=−3⇒Amin=−3 khi x=2x=2
B=4x2+4x+11=(2x+1)2+10≥10B=4x2+4x+11=(2x+1)2+10≥10
⇒Bmin=10⇒Bmin=10 khi x=−12x=−12
C=(x−1)(x+6)(x+2)(x+3)=(x2+5x−6)(x2+5x+6)C=(x−1)(x+6)(x+2)(x+3)=(x2+5x−6)(x2+5x+6)
=(x2+5x)2−36≥−36=(x2+5x)2−36≥−36
⇒Cmin=−36⇒Cmin=−36 khi [x=0x=−5[x=0x=−5
D=−x2−8x−16+21=21−(x+4)2≤21D=−x2−8x−16+21=21−(x+4)2≤21
⇒Cmax=21⇒Cmax=21 khi x=−4x=−4
E=−x2+4x−4+5=5−(x−2)2≤5E=−x2+4x−4+5=5−(x−2)2≤5
⇒Emax=5⇒Emax=5 khi x=2
![](https://rs.olm.vn/images/avt/0.png?1311)
Ta có:
\(\left(2x-1\right)^2+\left|2y-x\right|-8=12-5.2^2\)
=> \(\left(2x-1\right)^2+\left|2y-x\right|=12-20+8\)
=> \(\left(2x-1\right)^2+\left|2y-x\right|=0\)
nx:
\(\left(2x-1\right)^2\ge0với\forall x\)
\(\left|2y-x\right|\ge với\forall x,y\)
=> \(\left(2x-1\right)^2+\left|2y-x\right|\ge0với\forall x,y\)
Do đó:\(\left(2x-1\right)^2+\left|2y-x\right|=0\)
<=>\(\left\{\begin{matrix}2x-1=0\\2y-x=0\end{matrix}\right.\Leftrightarrow\left\{\begin{matrix}2x=1\\2y=2\end{matrix}\right.\)
<=>\(\left\{\begin{matrix}x=\frac{1}{2}\\2y=\frac{1}{2}\end{matrix}\right.\Leftrightarrow\left\{\begin{matrix}x=\frac{1}{2}\\y=\frac{1}{4}\end{matrix}\right.\)
Vậy x=1/2;y=1/4
![](https://rs.olm.vn/images/avt/0.png?1311)
\(\frac{x+11}{12}+\frac{x+11}{13}+\frac{x+11}{14}=\frac{x+11}{15}+\frac{x+11}{16}\)
\(\Rightarrow\frac{x+11}{12}+\frac{x+11}{13}+\frac{x+11}{14}-\frac{x+11}{15}-\frac{x+11}{16}=0\)
\(\Rightarrow\left(x+11\right)\left(\frac{1}{12}+\frac{1}{13}+\frac{1}{14}-\frac{1}{15}-\frac{1}{16}\right)=0\)
Mà \(\left(\frac{1}{12}+\frac{1}{13}+\frac{1}{14}-\frac{1}{15}-\frac{1}{16}\right)\ne0\)
\(\Rightarrow x+11=0\Rightarrow x=-11\)
![](https://rs.olm.vn/images/avt/0.png?1311)
Do \(\left|2x+3\right|=x+2\)
\(\Leftrightarrow\left[\begin{array}{nghiempt}2x+3=x+2\\2x+3=-\left(x+2\right)\end{array}\right.\)
\(\Leftrightarrow\left[\begin{array}{nghiempt}2x-x=2-3\\2x+3=-x-2\end{array}\right.\)
\(\Leftrightarrow\left[\begin{array}{nghiempt}x=-1\\2x+x=-2-3\end{array}\right.\)
\(\Leftrightarrow\left[\begin{array}{nghiempt}x=-1\\3x=-5\end{array}\right.\)
\(\Leftrightarrow\left[\begin{array}{nghiempt}x=-1\\x=-\frac{5}{3}\end{array}\right.\)
\(\left|2x+3\right|=x+2\) (1)
+)TH1: \(2x+3\ge0\Rightarrow x\ge-\frac{3}{2}\) yhif pt (1) trở thành
\(2x+3=x+2\Leftrightarrow x=-1\left(Tm\right)\)
+)TH2: \(2x+3< 0\Leftrightarrow x< -\frac{3}{2}\) thi pt (1) trở thành
\(-2x-3=x+2\Leftrightarrow-3x=5\Leftrightarrow x=-\frac{5}{3}\) (TM)